IDENTIFIKASI KERUSAKAN JALAN METODE PCI STUDI KASUS DI RUAS JALAN KABUPATEN GRESIK - siswoyo; Maliki, Akhmad; Soepriyono (Menara: Jurnal Teknik Sipil, 2024)
Research on level and types of road damage in Golokan – Ujung Pangkah Street, Gresik Regency using PCI (Pavement Condition Index) method aimed to determine the dominant degree and level of road damage as well as the sequence road priority which must be immediately taken the handling based on the results of road damage condition score of the roads. The PCI score is calculated by substracting the value of 100 with maximum CDV (Corrected Deduct Value), PCI = 100 – CDV = 100 – 22=78. Based on the results, it can be concluded that types of damages on Golokan – Ujung Pangkah Street, Gresik Regency is based on the ASTM D6433-11 and Guidance of Highways, the highest PCI score was 90 ( Excellent ) and the lowest one was 58 ( Good), and it is recommended for the damage handling to conduct routine maintenance in the form of 4 Cm and 7 Cm overlay works.